Prva najdba invazivne brestove grizlice, Aproceros leucopoda (Hymenoptera: Argidae) v Sloveniji - De Groot, Maarten (Gozdarski vestnik, 2012)
The first finding of the invasive ŽzigzagŽ sawfly Aprocerosleucopoda in Slovenia has been reported. The feeding tracks were first discovered in Rožna dolina near Nova Gorica in late September 2011. At the beginning of October, typical larva feeding symptoms were also observed on the localities Arboretum Volčji Potok and Botanical garden in Ljubljana. Most of the damaged trees wereField elms (U. minor), but also a few attacked Wych elms (U. glabra) were found. However, no signs of this species have been observed in the two checked places in Prekmurje yet. The biology of A. leucopoda and the possibilities of its control are discussed.
Keywords: Hymenoptera; tujerodne vrste; invazivne vrste; Argidae; Aproceros leucopoda; Ulmus spp.; Slovenia; Slovenija